Experiencing Phonaesthesia in the Novel The God of Small Things: Exploring the Role of Phonology and Sound Mechanism in The God of Small Things (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present paper is an attempt to investigate how phonology plays an important role in givingthat extra edge to the text. The author uses sound mechanism to make the reader hear what is happening.There is deliberate arrangement of phonemes, sound patterns, preference of certain specific consonantsover others to suit the context.